Digital Leadership: Develop Perceived organizational Support in The Perception of Talent Mobility at Employment Social Security Supervisory Agency - Aditya Warman; Affandi, Muhammad Joko; Sukmawati, Anggraini; Maarif, Mohammad Syamsul; Alfiany, Hana; Hanifah, Reinanda Isfania (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study analyzes the perspective of employees who consider the implementation of rotation and transfer as a disciplinary action in relation to the formation of perceived organizational support which is influenced by commitment and fairness to the organization and recommends a digital approach as a solution to address the issue. Data is collected through quantitative surveys from 4.523 employees at several offices of the Employees Social Security Sistem (BPJS Ketenagakerjaan). Organizational support is related to organizational justice and organizational commitment as the determining factors of employee acceptance of the implementation of job rotation and transfer. It resulted in different perceptions from the initial goals of job rotation and job transfer. The study suggests system digitalization in the implementation of leadership in the organization to address the issues in a broad reach. Keywords: job rotation and transfer, perceived organizational support, digital leadership, organizational commitment, organizational justice